Therapeutic Hypothermia Modulates the Relationships Between Indicators of Severity of Neonatal Hypoxic Ischemic Encephalopathy and Serum Biomarkers - Chavez-Valdez, Raul; Miller, Sarah; Spahic, Harisa; Vaidya, Dhananjay; Parkinson, Charlamaine; Dietrick, Barbara; Brooks, Sandra; Gerner, Gwendolyn J.; Tekes, Aylin; Graham, Ernest M.; Northington, Frances J.; Everett, Allen D. (Frontiers in Neurology, 2021)
Objective: To determine the changes due to therapeutic hypothermia (TH) exposure in the strength of association between traditional clinical and biochemical indicators of severity of neonatal hypoxic-ischemic encephalopathy (HIE) and serum biomarkers. We hypothesized that culmination of TH changes the strength of the relationships between traditional indicators of severity of HIE and serum biomarkers. Methods: This was a single-center observational cohort study of 178 neonates with HIE treated with TH and followed with serum biomarkers: (i) brain-derived neurotrophic factor (BDNF) and vascular endothelial growth factor (VEGF) (neurotrophins); (ii) tau and glial fibrillary acidic protein (GFAP) (neural cell injury); and (iii) interleukin 6 (IL-6), IL-8, and IL-10 (cytokines), during their first week of life. Adjusted mixed-effect models tested associations with HIE indicators in relation to TH exposure. Results: At admission, lower Apgar scores and base excess (BE) and higher lactate and nucleated red blood cell (NRBC) count correlated with higher Sarnat scores. These indicators of worse HIE severity, including higher Sarnat score, correlated with lower VEGF and higher tau, GFAP, and IL-10 levels at different time points. Within the first 24 h of life, patients with a Sarnat score >2 had lower VEGF levels, whereas only those with score of 3 also had higher GFAP and IL-10 levels. Tau levels increased during TH in patients with Sarnat score of 3, whereas tau and GFAP increased after TH in those with scores of 2. After adjustments, lower VEGF levels during TH and higher tau, GFAP, and IL-10 levels during and after TH were associated with worse Sarnat scores. Tau and GFAP relationship with Sarnat score became stronger after TH. Conclusion: Therapeutic hypothermia exerts an independent modulatory effect in the relationships between traditional indicators of severity of HIE and serum biomarkers after adjustments. Thus, the timing of biomarker testing in relation to TH exposure must be carefully considered if biomarkers are proposed for patient stratification in novel clinical trials.